Improving the Quality of Education Through Environmentally Based Learning - zahrah, syarifah; Susanto, Teguh Trianung Djoko; Pratama, M. Zulfakar; Aisyah, Jihan; Kurniawan, Andi (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
Environmental education is education that helps individuals become more familiar with their environment, develop responsible behavior and environmental skills to improve the quality of the environment. One effort that can be made to improve the quality of the environment is to provide environmental education from an early age through the education process. This paper aims to analyze improving the quality of environmentally based education and examine studies of environmentally based education in improving the quality of education. Increasing insight into improving the quality of environment-based education based on a literature review shows that to produce quality graduates there are several factors that need to be achieved, such as teacher quality, curriculum, educational facilities and educational management which are determining factors in achieving good goals. education quality. The development of an environment-based learning model is identified as an important step to improve students' learning skills and experiences